A randomised controlled trial of non-invasive ventilation compared with extracorporeal carbon dioxide removal for acute hypercapnic exacerbations of chronic obstructive pulmonary disease - Nicholas A. Barrett; Nicholas Hart; Kathleen J. R. Daly; Martina Marotti; Eirini Kostakou; Chris Carlin; Stephanie Lua; Suveer Singh; Andrew Bentley; Abdel Douiri; Luigi Camporota (Annals of Intensive Care, 2022)
Abstract Background Patients presenting with acute hypercapnic respiratory failure due to exacerbations of chronic obstructive pulmonary disease (AECOPD) are typically managed with non-invasive ventilation (NIV). The impact of low-flow extracorporeal carbon dioxide removal (ECCO2R) on outcome in these patients has not been explored in randomised trials. Methods Open-label randomised trial comparing NIV (NIV arm) with ECCO2R (ECCO2R arm) in patients with AECOPD at high risk of NIV failure (pH < 7.30 after ≥ 1 h of NIV). The primary endpoint was time to cessation of NIV. Secondary outcomes included device tolerance and complications, changes in arterial blood gases, hospital survival. Results Eighteen patients (median age 67.5, IQR (61.5–71) years; median GOLD stage 3 were enrolled (nine in each arm). Time to NIV discontinuation was shorter with ECCO2R (7:00 (6:18–8:30) vs 24:30 (18:15–49:45) h, p = 0.004). Arterial pH was higher with ECCO2R at 4 h post-randomisation (7.35 (7.31–7.37) vs 7.25 (7.21–7.26), p < 0.001). Partial pressure of arterial CO2 (PaCO2) was significantly lower with ECCO2R at 4 h (6.8 (6.2–7.15) vs 8.3 (7.74–9.3) kPa; p = 0.024). Dyspnoea and comfort both rapidly improved with commencement of ECCO2R. There were no severe or life-threatening complications in the study population. There were no episodes of major bleeding or red blood cell transfusion in either group. ICU and hospital length of stay were longer with ECCO2R, and there was no difference in 90-day mortality or functional outcomes at follow-up. Interpretation There is evidence of benefit associated with ECCO2R with time to improvement in respiratory acidosis, in respiratory physiology and an immediate improvement in patient comfort and dyspnoea with commencement of ECCO2R. In addition, there was minimal clinically significant adverse events associated with ECCO2R use in patients with AECOPD at risk of failing or not tolerating NIV. However, the ICU and hospital lengths of stay were longer in the ECCO2R for similar outcomes. Trial registration The trial is prospectively registered on ClinicalTrials.gov: NCT02086084. Registered on 13th March 2014, https://clinicaltrials.gov/ct2/show/NCT02086084?cond=ecco2r&draw=2&rank=8